2012
DOI: 10.7251/agren1204667s
|View full text |Cite
|
Sign up to set email alerts
|

Determining Some Exterior and Interior Quality Traits of Japanese Quail Eggs (Coturnix japonica)

Abstract: The aim of this research was to determine some exterior and interior quality traits of Japanese quail eggs. A total of 60 Japanese quail eggs were collected from two different farms near Novi Sad, and the eggs quality traits were tested in the laboratory of poultry science at the Department of Animal Science of the Faculty of Agriculture in Novi Sad. The egg weight, albumen weight, yolk weight, shell weight, shell breaking force, shell thickness, albumen height and egg yolk colour were determined. The external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Our results shown in Table 10 revealed that there were significant increase in albumin weight and albumin percent in battery cage than floor pen reared quail. These results are in agreement with (Sari et al 2012) and Mirjana et al (2012). Shell Thickness, weight and percentage: The most important quality traits of the egg shell are its thickness.…”
Section: Effect Of Housing System On Egg Quality (Eq) Traitssupporting
confidence: 92%
“…Our results shown in Table 10 revealed that there were significant increase in albumin weight and albumin percent in battery cage than floor pen reared quail. These results are in agreement with (Sari et al 2012) and Mirjana et al (2012). Shell Thickness, weight and percentage: The most important quality traits of the egg shell are its thickness.…”
Section: Effect Of Housing System On Egg Quality (Eq) Traitssupporting
confidence: 92%
“…Average eggshell weight was determined as 0.85 g in the present study, which was previously reported as 0.84 g by Kul & Seker (2004), 0.96 g by Sezer (2007), 1.00 (0.84-1.15 g) by Alkanet al (2010), 1.73-1.80 g by Stojčić et al (2012), 0.94 g by Ojedapo (2013), 1.09 g by Alasahan et al (2015), and 1.12-1.21g by Hanusová et al (2016). In the present study, albumen and yolk weights were determined as 6.93 g and 4.45 g, respectively, and previously reported as 6.75 g and 3.69 g by Kul & Seker (2004), 6.07-7.08 g and 3.42-3.72 g by Stojčić et al (2012), 6.35-7.44 g and 3.86-4.54 g by Ozdemir & Inci (2012), 4.95 g…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, the average egg weight of the yellow Japanese quail (Coturnix japonica) was determined 12.23 g. The following weight values were previously reported: 11.28 g by Kul & Seker (2004); 11.06 g by Sezer (2007); 11.43 g by Alkan et al (2010); 11.14-12.84 g by Ozdemir & Inci, (2012); 11.52-12.30 g by Stojčić et al (2012); 8.19 g by Ojedapo (2013); 13.06 g and 11.48 g for meat and layer types, respectively, by Hrncar et al (2014); 12.70 g by Alasahan et al (2015); and 12.20-13.26 g by Hanusová et al (2016). Average eggshell weight was determined as 0.85 g in the present study, which was previously reported as 0.84 g by Kul & Seker (2004), 0.96 g by Sezer (2007), 1.00 (0.84-1.15 g) by Alkanet al (2010), 1.73-1.80 g by Stojčić et al (2012), 0.94 g by Ojedapo (2013), 1.09 g by Alasahan et al (2015), and 1.12-1.21g by Hanusová et al (2016). In the present study, albumen and yolk weights were determined as 6.93 g and 4.45 g, respectively, and previously reported as 6.75 g and 3.69 g by Kul & Seker (2004), 6.07-7.08 g and 3.42-3.72 g by Stojčić et al (2012), 6.35-7.44 g and 3.86-4.54 g by Ozdemir & Inci (2012), 4.95 g…”
Section: Discussionmentioning
confidence: 51%